Binding Inhibition Between Igf1r and Igf1 by Catechin of Black Tea - Lina Firdausi; M Rasjad Indra; fatchiyah . (Journal of Tropical Life Science, 2012)
The natural compound of black tea is used as an alternative of obesity therapies in the world; particularly, the catechin family in tea leaves which has bioactive compounds such as EC, EGC and EGCG. Their bioactivity contributes to inhibit the ligand of Insulin-Like Growth Factor I Receptor (Igf-1r) binding-region to Igf-1 protein. To elucidate the inhibiton of Igf-1 expression and proliferating of Rattus norvegicus strain wistar adipose cell using black tea solution. The research used Rattus norvegicus strain wistar. After a 90-day treatment, the adipose tissues were picked up from the viscera of each experimental animal, and then the adipose tissues were embedded by paraffin. The paraffin sections were determined through immunohistochemistry with anti-Igf-1 antiserum, and were also analyzed through hematoxylin-eosin. A protein sequence of Igf-1, Igf-1r, and 3D structure of EC, EGC and EGCG from Gene Bank sites were used during in silico analysis. The sequences were aligned by BLAST program to identify the conserve and variable domain of IGF-1 protein isoforms. The 3D structures of IGF-1 and IGF-1R were constructed using Phyre program. The ligand among the 3D structures of IGF-1, IGF-1R and catechin compounds were analyzed using Hex 5.1 docking program. The data showed that the Igf-1 expression of adipose cells was reduced at 0,03 g/ml BTS and 0,045 g/ml BTS treatments. The result of BLAST analysis showed that IGF-1 (a, b, c, and d) isoforms conserved a domain from amino acid no 22 until 134; and this region was a variable region. The EGCG bound L1 domain of IGF-1R with E-total -235.3 KJ/mol which was lower than EC (-208,4 KJ/mol) and EGC (-142 KJ/mol). The total energy of IGF-1 (a, b, c, but not d isoform) which interacted with EGCG was around -223.7 KJ/mol, EC is -205.6 KJ/mol and EGC was -191.7 KJ/mol. However, EC, EGC and EGCG was only able to prevent the interaction between the L1 of IGF-1R with IGF-1 protein, but not the opposite.Keywords: Adipose cell, black-tea, proliferation, catechin, IGF-1, IGF-1R, inhibition, docking